Pemanfaatan Ekstrak Daun Sirih (Piper betle L.) dalam Pembuatan Hand Sanitizer Berbasis Pemberdayaan Masyarakat Desa - M. Henityo Agung As’adi; Tita Aulya Nofira JK; Chika Putri; Elly Yulia; Syahdila Dwi Saputri; Ameliya Gustina; Risky Dwi Amanda; Intan Apriana Rahmadani; Puja Melisa Ramadhanti (Universitas Baiturrahim, 2026)
The increasing demand for effective and safe antiseptic products has encouraged the development of natural-based hand sanitizers as an alternative to synthetic chemical products. Betel leaves (Piper betle L.) contain bioactive compounds such as flavonoids, tannins, saponins, eugenol, and essential oils that have been proven to have antibacterial activity against various pathogenic microorganisms. This community service activity aims to increase the knowledge and skills of the community of Sinar Harapan Hamlet, Muhajirin Village, Jambi Luar Kota District in making hand sanitizers from boiled betel leaf extract. The activity was carried out on January 22, 2026, using counseling methods, direct demonstrations, and group practice involving 25 participants from among housewives and health cadres. The manufacturing process includes boiling betel leaves in distilled water, filtering the filtrate, and mixing with 70% alcohol and glycerin as a humectant. The results of the activity showed that the community was able to practice making hand sanitizer independently and produced 20 bottles of 50 ml products that were distributed to residents. The enthusiasm and active participation of participants reflected the high acceptance of health innovations based on local natural ingredients. This activity makes a positive contribution to increasing community independence and supporting the implementation of clean and healthy living behaviors (PHBS).